Egg Development of the Ussurian Bullhead Fish, Leiocassis ussuriensis (Pisces: Bagridae) and Morphological Development of Its Larvae and Juveniles - Park, Jae-Min (Dev Reprod, 2015)
This study was examined the ovogenesis of Ussurian bullhead, Leiocassis ussuriensis and the morphological development of its larvae and juveniles and to use the results as basic information for the preservation of species and resource enhancement. For artificial egg collection, human chorionic gonadotropin (HCG) was injected at a rate of 10 IU per gram of fish weight. During breeding period, water temperature maintained at 24.5~26.5°C (mean 25.0±0.05°C). The process of ovogenesis reached the two-cell stage in 50 minutes after fertilization. In 73 hours of fertilization the movement of the embryoid body became active state and the larvae began to hatch from the tail through the oolemma. Length of prelarvae were 6.33~6.50 mm long (mean 6.40±0.06 mm) just after hatching having yolk with their mouth not opened. After thirty eight days of hatching, juveniles were 30.6∼32.5 mm long (mean 31.5±0.65 mm). The color was dark yellowish brown throughout the entire body, and the number of caudal fin rays developed to thirty six perfectly.